Forum on parasite vaccines: a tribute to Declan McKeever. Issue 2 (February 2015) - Perry, Brian; Innes, Elisabeth A.
<x xml:space="preserve">Abstract</x> Professor Declan McKeever, a much-loved colleague and friend who died in January 2014, devoted much of his professional life to developing vaccines against tick-borne diseases of cattle. A conference was held at Hatfield House on the 21st October, 2014, bringing together colleagues from across the world to discuss the challenges of parasite control and to celebrate Declan's contributions and achievements.